1970
DOI: 10.1104/pp.46.2.324
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Transpiration Resistances of Xanthium Leaves as Affected by Air Temperature, Humidity, and Wind Speed

Abstract: We undertook this investigation in order to find out whether the partitioning of energy between transpiration and convection is significantly controlled by changes in the transpiration resistance within the leaf occurring in response to changes in the physical environment of the leaf. We restricted our investigation to a variation of temperature, moisture content, and movement of the air. The experiments were done under strictly controlled conditions with only one environmental factor changing at a time. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0
1

Year Published

1972
1972
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(64 citation statements)
references
References 10 publications
7
56
0
1
Order By: Relevance
“…4), and that the extent to which stomata respond to humidity varies between species (12). Reduced stomatal response to humidity at higher temperatures is also apparent in the data of Drake et al (5). The small stomatal response to ambient humidity obtained by Wilson (28) (Fig.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…4), and that the extent to which stomata respond to humidity varies between species (12). Reduced stomatal response to humidity at higher temperatures is also apparent in the data of Drake et al (5). The small stomatal response to ambient humidity obtained by Wilson (28) (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…In earlier work, when progressively drier air resulted in stomatal closure, it was frequently assumed that the stomatal closure was caused by changes in bulk leaf water status (5). However, the studies of Schulze et al (23) with apricot clearly demonstrated that stomata may respond to humidity independently of effects that humidity might have on bulk leaf water status.…”
Section: Discussionmentioning
confidence: 93%
“…After the pretreatment had been completed, plants were removed from the growth chamber, and all but the leaf having a total surface area closest to 160 cm2 were excised. To keep it from fluttering, a wire loop, just (2) where u and 1 refer to upper and lower leaf surfaces. The value of the leaf resistance for each surface was the average of three measurements.…”
Section: Resultsmentioning
confidence: 99%
“…STOMATAL CONDUCTANCE AND THE ENERGY BUDGET Reduced transpiration alters partitioning of energy between latent heat loss and convective exchange, potentially increasing leaf temperature (63). Elevating C a to 55 Pa consistently decreased g s and increased canopy temperature of cotton about 1°C (173).…”
Section: Acclimation Of G S To Elevated C Amentioning
confidence: 99%